Rediscovery of presumed extinct Isoetes divyadarshanii (Isoetaceae—Lycopodiopsida) in India: New insight on its morphology, taxonomy and conservation status - Singh, Sarvesh Kumar; Brunton, Daniel F.; Shukla, Pradeep Kumar; Sokoloff, Paul C.; Shukla, Santosh Kumar; Patil, Anant Prakash; Dubey, Nawal Kishor (Phytotaxa, 2025)
A population of Isoetes divyadarshanii, a species previously known only from its type location in Maharashtra State, India and considered extinct since at least 2013, was discovered on the Sada Plateau in the Belagavi District of Karnataka state, India in October 2023. This represents a significant disjunction (over 465 km) from its type location into a different phytogeographic division of the Indian subcontinent. The new information provided by this discovery permits verification of critical elements of the original description. It also allows for an updated and more precise description of the morphology, ecology and taxonomy of this poorly understood taxon. A detailed morphological comparison with closely related taxa, especially I. udupiensis, is presented. The cytology of the new population is reported (2n = 2× = 22) and the IUCN conservation status criteria designation of the species is revised from Critically Endangered (Extinct) to Endangered. Finally, the phytogeographic implications of this new discovery are discussed.